(untitled) (Nepalese Journal of Development and Rural Studies, 2024)
Tourism may be an effective instrument for advancing sustainable development through generating employment and preserving cultural and natural resources. This article is based on the review using descriptive statistics method that includes scientific readings and publications about tourism and its revenue in the particular context of Nepal. The International Recommendations for Tourism Statistics 2008 provides the basic concepts and definitions concerning the different aspects of tourism such as international tourism revenue, which can be viewed through receipt (% of export) and expenditure (% of import). Before the COVID-19 pandemic spread, revenue from international tourism was recorded the lowest but started improving gradually. Aligning tourism revenue with development strategies, this study concludes that revenue generation serves as a crucial driver for tourism growth in developing countries like Nepal. Examining various quality-of-life measurement models allows for the identification of best practices, facilitating the adaptation of tourism development approaches to specific contexts.